2017
DOI: 10.1007/s00430-017-0501-6
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Quantiferon cytokines for diagnosis of children with active tuberculosis and HIV co-infection in Ghana

Abstract: IFN-γ release assays (IGRAs) often present false-negative or indeterminate results in children with tuberculosis. HIV co-infection may contribute to decreased sensitivity of IGRAs by impairing T-cell IFN-γ expression. Measurement of alternative cytokines in QuantiFERON (QFT) supernatants can circumvent the IFN-γ-dependency and may improve QFT sensitivity. We aimed to identify additional cytokines from QFT supernatants for detection of Mycobacterium tuberculosis infection in children with tuberculosis and HIV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
11
1
Order By: Relevance
“…QFT results were negative or indeterminate for the majority of tuberculosis patients and healthy contacts. This outcome confirmed own previous studies that showed low sensitivity of QFT tests for detection of Mtb infection in children with tuberculosis from Ghana (6). In contrast, a parallel study in children with tuberculosis and LTBI from Germany showed almost optimal sensitivity of the QFT (7).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…QFT results were negative or indeterminate for the majority of tuberculosis patients and healthy contacts. This outcome confirmed own previous studies that showed low sensitivity of QFT tests for detection of Mtb infection in children with tuberculosis from Ghana (6). In contrast, a parallel study in children with tuberculosis and LTBI from Germany showed almost optimal sensitivity of the QFT (7).…”
Section: Discussionsupporting
confidence: 92%
“…But by implication, these studies excluded tuberculosis patients and HCs that were false negative in QFT/IGRA. Since previous studies clearly demonstrated that also IFN-γ negative CD4 + T cells producing alternative cytokines contribute to immunity against Mtb (6, 30), we hypothesize that negative QFT/IGRA results do not preclude Mtb infection.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Interferon-gamma (IFN-γ) release assays (IGRAs) are a standard diagnostic tool in high-income countries with low incidence rates. However, limited sensitivity of IGRAs in young children and immune-compromised individuals as well as potentially in some high-endemic countries highlight the need for additional assays and/or more complex biomarker signatures [1,2].…”
mentioning
confidence: 99%